Assessment of morpho-genetic diversity of guava (Psidium guajava) hybrids and genotypes - N, NIKHIL H; GOSWAMI, AMIT KUMAR; SINGH, S K; KUMAR, CHAVLESH; GOSWAMI, SUNEHA; SINGH, RAKESH; BHARADWAJ, C; MAURYA, NAVEEN KUMAR (The Indian Journal of Agricultural Sciences, 2021)
A total of 20 diverse guava genotypes, including the newly bred hybrids were characterized using the morphological, physio-biochemical parameters and microsatellite markers at ICAR-IARI, New Delhi during 2018-19. Most of the qualitative morphological and physio-biochemical parameters had a coefficient of variation value >20%, which indicated substantial diversity. The longest leaves (14.87 cm) were recorded in Lalit, which was statistically at par with Pant Prabhat (14.67 cm), while amongst the hybrids, it is in GH 2018-10 (13.93 cm). The maximum leaf area was recorded in Pant Prabhat (60.33 cm2) while amongst hybrids it was in GH 2018-2 (53.40 cm2). The highest stomatal conductance and net photosynthetic rate was recorded in guava genotype Shweta (9.63 μmol/m2/s) (0.25 mol/m2/sec) while amongst the hybrids it was in GH 2018-8 (8.73μmol/m2/s) (0.26 mol/m2/sec), respectively. The mean genetic diversity indices, viz. major allelic frequency, number of alleles, gene diversity, heterozygosity and polymorphic information content of eight SSRs were 0.497, 3.75, 0.599, 0.071 and 0.542, respectively among the guava genotypes. Furthermore, the eight SSRs based Neighbour-joining (N-J) tree separated the newly bred guava hybrids into different clusters, clades and out-groups.